Gambaran Radiologi Magnetic Resonance Imaging (MRI) pada Pasien Meningioma di Rumah Sakit Daerah K.R.M.T Wongsonegoro - Maryani, Luh Putu Endyah Santi; Nathaniel, Fernando; Wijaya, Dean Ascha; Firmansyah, Yohanes; Yogie, Giovanno Sebastian (Universitas Malahayati, 2023)
ABSTRACT Meningioma, the most prevalent tumor in central nervous system, can be thoroughly evaluated using contrast MRI. This cross-sectional study aimed to analyze radiological characteristics of meningioma patients who underwent contrast-enhanced head MRI at K.R.M.T Wongsonegoro Regional Hospital. The patients were selected based on total sampling criteria, using medical records data from January to June 2023. The study examined various variables such as primary and secondary meningioma lesions, lesion size, location, increased intracranial pressure, midline shift, infarction, cranial nerve defects, and sinusitis. Data were presented descriptively. Among 30 respondents, average age was 49.33 years, and majority were females (96.7%). Most common location for primary meningiomas was right parafalcine region (16.7%). Average dimensions of primary meningioma lesions in the anterior-posterior, lateral-lateral, and cranial-caudal directions were 4.93 cm, 4.51 cm, and 4.43 cm, respectively. Meningomatosis was the predominant imaging finding in 33.3% of respondents, while 26.7% had secondary meningioma lesions. On average, the midline shift was 5.54 mm, with 93.3% of respondents experiencing midline shift, most frequently towards left side (53.3%). Clinical and radiological reviews demonstrated that all patients had increased intracranial pressure (ICP), among them, 9.9% experienced incidents of infarction, 13.3% had defects in cranial nerve II, and 43.3% had maxillary sinusitis. The conclusion of this study is that the location of meningioma generally varies with typical symptoms in the form of a midline shift and an increase in ICP Keywords : Central Nervous System, Head Tumor, Meningioma, MRI ABSTRAK Meningioma merupakan tumor sistem saraf pusat yang paling sering. MRI kontras mampu memberikan evaluasi cukup lengkap terhadap meningioma. Penelitian potong lintang ini bertujuan untuk mengetahui gambaran radiologi pasien meningioma yang menjalani pemeriksaan MRI kepala dengan kontras di Rumah Sakit Daerah K.R.M.T Wongsonegoro yang dipilih sesuai kriteria secara total sampling menggunakan data rekam medis pada periode waktu Januari 2023 sampai Juni 2023. Variabel dalam penelitian ini yaitu lesi meningioma primer dan sekunder, ukuran lesi meningioma, letak lesi meningioma, peningkatan tekanan intrakranial, midline shift, insiden infark, defek nervus kranial, dan sinusitis. Data disajikan dalam bentuk deskriptif. Dari 30 responden, rerata usia adalah 49,33 tahun dan didominasi oleh perempuan (96,7%). Lokasi meningioma primer umumnya di parafalcine kanan (16,7%), ukuran meningioma primer secara anterior-posterior, lateral-lateral, cranial-kaudal berturut-turut adalah 4,93 cm, 4,51 cm, dan 4,43 cm, dominasi gambaran meningioma adalah meningomatosis pada 33,3% responden, serta 26,7% responden memiliki lesi meningioma sekunder. Rerata midline shift sebesar 5,54 mm pada 93,3% responden dan umumnya bergeser ke sisi kiri (53,3%). Peninjauan dari segi klinis dan radiologi ditemukan bahwa seluruh pasien mengalami peningkatan tekanan intrakranial (TIK), terdapat 9,9% responden mengalami insiden infark, 13,3% responden mengalami defek pada nervus kranial II, dan 43,3% responden mengalami sinusitis maksilaris. Kesimpulan penelitian ini berupa letak meningioma umumnya bervariasi dengan gejala yang khas berupa midline shift dan peningkatan TIK Kata Kunci: Meningioma, MRI, Sistem Saraf Pusat, Tumor Otak